The Influence of Transformational Leadership and Transactional Leadership on Employee Performance with Work Motivation as an Intervening Variable - Lishandy, Nabila Putri; Musadieq, Mochammad Al; Hutahayan, Benny (Sekolah Pascasarjana Universitas Brawijaya, 2023)
Leadership serves as the reason for high work motivation and performance of individuals in their work. A leader's role significantly influences subordinates, determining an organization's progress. This research aims to explain and analyze the influence of transformational and transactional leadership on employee performance, with work motivation as an intervening variable. This study is an explanatory research conducted at pt. Sreeya sewu indonesia tbk-sidoarjo. The population for this research consists of 267 employees, with a sample of 160 employees using proportional stratified random sampling. The analysis method employed in this study is path analysis. This research indicates that transformational and transactional leadership impact performance, and the motivation variable can mediate the relationship between transformational leadership and performance. This research provides practical implications to assist organizations in achieving better effectiveness and efficiency through a more focused leadership approach and empowering employees with solid motivation. Keywords : transformational leadership, transactional leadership, motivation, performance